2012
DOI: 10.1029/2011gc003883
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the kinematics of the India‐Eurasia collision from global geodynamic models

Abstract: [1] The Eocene India-Eurasia collision is a first order tectonic event whose nature and chronology remains controversial. We test two end-member collision scenarios using coupled global plate motion-subduction models. The first, conventional model, invokes a continental collision soon after $60 Ma between a maximum extent Greater India and an Andean-style Eurasian margin. The alternative scenario involves a collision between a minimum extent Greater India and a NeoTethyan back-arc at $60 Ma that is subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 125 publications
(184 reference statements)
2
76
0
Order By: Relevance
“…This coincides with the significant drop in India-Eurasia convergence from 60-50 Ma (India-Kohistan/KLA, Fig. 7b) (Zahirovic et al, 2012) and was likely due to the buoyancy of Indian continental crust impeding subduction at the intra-oceanic arc. Andean-style subduction re-initiated along southern Lhasa by 65 Ma (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
See 2 more Smart Citations
“…This coincides with the significant drop in India-Eurasia convergence from 60-50 Ma (India-Kohistan/KLA, Fig. 7b) (Zahirovic et al, 2012) and was likely due to the buoyancy of Indian continental crust impeding subduction at the intra-oceanic arc. Andean-style subduction re-initiated along southern Lhasa by 65 Ma (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
“…6k), and coincides with a second significant drop in India-Eurasia convergence rates at ~43 Ma (Fig. 7b) and reorganization of seafloor spreading in the Indian Ocean (Lee and Lawver, 1995;Zahirovic et al, 2012), coupling Indian and Australian plates (Liu et al, 1983), which began to move to north-…”
Section: Accepted Manuscriptmentioning
confidence: 87%
See 1 more Smart Citation
“…Such an approach can be verified by linking geodynamic models to plate reconstructions in order to reproduce present-day mantle structure that can be validated using seismic tomography. Interpretations of subducted slab volumes have shown that alternative subduction scenarios can be tested (Van der Voo et al, 1999;Zahirovic et al, 2012), whilst also providing a possible absolute reference frame in the absence of reliable hotspot tracks in premid-Cretaceous times (van der Meer et al, 2010).…”
Section: Limitations Of Plate Reconstructionsmentioning
confidence: 98%
“…such as in [6,20]), preventing slab pull to be transmitted. In such case, the necessary geodynamic force to move India northward would be annihilated.…”
Section: The Argo Abyssal Plainmentioning
confidence: 99%